2020
DOI: 10.1186/s12870-020-02487-0
|View full text |Cite
|
Sign up to set email alerts
|

Cold priming uncouples light- and cold-regulation of gene expression in Arabidopsis thaliana

Abstract: Background: The majority of stress-sensitive genes responds to cold and high light in the same direction, if plants face the stresses for the first time. As shown recently for a small selection of genes of the core environmental stress response cluster, pre-treatment of Arabidopsis thaliana with a 24 h long 4°C cold stimulus modifies cold regulation of gene expression for up to a week at 20°C, although the primary cold effects are reverted within the first 24 h. Such memory-based regulation is called priming. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 92 publications
(149 reference statements)
6
24
0
Order By: Relevance
“…This may indicate that first waterlogging treatment enhanced tolerance to recurring waterlogging stress in the sensitive accession. An increased number of DEGs in primed plants, compared to non-primed plants, was also observed in rice, where salt shock was used as the priming factor [ 64 ] and in radish, where cold priming was applied [ 65 ]. To the best of our knowledge, there is no information on the differential number of regulated genes between plants treated once with hypoxic stress and plants treated again with stress, thus these results are novel and unique in the area of waterlogging tolerance in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that first waterlogging treatment enhanced tolerance to recurring waterlogging stress in the sensitive accession. An increased number of DEGs in primed plants, compared to non-primed plants, was also observed in rice, where salt shock was used as the priming factor [ 64 ] and in radish, where cold priming was applied [ 65 ]. To the best of our knowledge, there is no information on the differential number of regulated genes between plants treated once with hypoxic stress and plants treated again with stress, thus these results are novel and unique in the area of waterlogging tolerance in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have shown that a 24-h temperature shift from 20 °C to 4 °C under short-day conditions does not support cold-activation of CBF s (encoding C-repeat binding factors) or their target genes in Arabidopsis upon cold-triggering at 4 °C after a lag-phase of 5 d at 20 °C in 4-week-old plants ( van Buer et al , 2016 ), but it does result in higher expression of defence-regulated genes ( Bittner et al , 2020 ) and in decreased susceptibility to pathogens ( Griebel et al , 2020 , Preprint). The same genes are not induced in cold-primed plants by heat-filtered, high-light conditions, and some are even inversely regulated by cold-priming in response to the high light, for example the pathogen responsive genes PR4 (At3g04720) and PCC1 (At3g22231) ( Bittner et al , 2020 ). Other genes are only priming-sensitive in the cold, but not in the light, for example the light- and cold-inducible genes for the stress-signalling mediating zinc-finger transcription factors ZAT6 (At5g04340), ZAT10 (At1g27730; STZ ), and ZAT12 (At5g59820) ( Bittner et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The same genes are not induced in cold-primed plants by heat-filtered, high-light conditions, and some are even inversely regulated by cold-priming in response to the high light, for example the pathogen responsive genes PR4 (At3g04720) and PCC1 (At3g22231) ( Bittner et al , 2020 ). Other genes are only priming-sensitive in the cold, but not in the light, for example the light- and cold-inducible genes for the stress-signalling mediating zinc-finger transcription factors ZAT6 (At5g04340), ZAT10 (At1g27730; STZ ), and ZAT12 (At5g59820) ( Bittner et al , 2020 ). Although epigenetic regulation by DNA and/or histone acetylation or methylation can mediate priming ( Hilker et al , 2016 ; Avramova, 2019 ; Baier et al , 2019 ; Friedrich et al , 2019 ), the majority of shifts in gene expression after short abiotic priming events result from transcriptional regulation, for example after 2 h of dehydration stress, 60 min of excess light, or 24 h of cold ( Ding et al , 2013 ; Ganguly et al , 2019 ; van Buer et al , 2019 ; Bittner et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations